USING THE ANALYTIC SIGNAL METHOD OF GRAVITY GRADIENT TENSOR (GGT) TO DETERMINE THE LOCATION AND DEPTH OF THE FAULTS IN THE PRE-CENOZOIC BASEMENT ROCKS OF THE RED RIVER TROUGH - Dung*, Nguyen Kim; Thanh, Do Duc (Vietnam Journal of Earth Sciences, 2016)
In this paper, we present the study results of using the directional analytic signal method of gravity gradient tensor (GGT) and the Euler deconvolution of the directional analytic signals to determine location and estimate the depth of fault systems in the Pre-Cenozoic basement in order to improve the efficiency of Pre-Cenozoic basement structure. The method is tested on the 3D digital model, which shows that not only the location and depth of resources are determined but also can overcome undue interference, which could be met in the previous analytic signal methods. To study more about the applicability of the method, we applied the method for the gravity anomaly data of Red River Trough. Obtained preliminary results have shown the location of major faults in the region: Song Lo fault, Song Chay fault, Red River fault, etc. and initially (in the first time), by this method, the depth of over 10 km the fault persists. This depth is deeper than the depth of the surface of Cenozoic boundary determined by other methods, proves that the faults appear in the Pre-Cenozoic basement. References Mickus,K.L., Juan Homero Hinojosa, 2001. The complete gravity gradient tensor derived from the vertical component of gravity: a Fourier transform technique. Journal of Applied Geophysics 46, 159-174. Beiki M, 2010. Analytic signals of gravity gradient tensor and their application to estimate source location. Geophysics, Vol.75, No.6, 159-174. Beiki M, 2011. New techniques for estimation of source parameters. Uppsala Universitet. Beiki M., Pedersen, L.B., 2010. Eigenvector analysis of gravity gradient tensor to locate geologic bodies. Geophysics 75, I37-I49. Bhaskara Rao, D., Prakash, M.I., and Ramesh Babu, N., 1990. 3 and D modeling of gravity anomalies with variable density contrast. Geophys. Prosp, Vol.38, 411-422. Blakely, R. J., and R. W. Simpson, 1986. Approximating edges of source bodies from magnetic or gravity anomalies: Geophysics,51, 1494-1498,doi: 10.1190/1.1442197. Bui Cong Que, Hoang Van Vuong, 1996. Investigation on the density distribution of Pre-Cenozoic fundament in the South - East Viet Nam shelf by the volumetric structural modelling method of the Earth crust. Proceeding of marine geology and geophysics study works, Vol, 2, Publisher of Science and Engineering, 1996, 277-285. Cao Dinh Trieu, Pham Huy Long, 2002. Tectonic fault in Vietnam. Publisher of Science and Engineering. Cao Dinh Trieu, Pham Nam Hung, 2008. Some characteristics of the geological structure in the Cenozoic in southwest of Hanoi trough based on data analysis of gravity and other geological-geophysical data. Debeglia, N., and J. Corpel, 1997. Automatic 3-D interpretation of potential field data using analytic signal derivatives. Geophysics,62, 87-96, doi:10.1190/1.1444149. Do Duc Thanh, Nguyen Kim Dung, 2013. Determine density contribution of basement rock by modeling of 3D gravity inversion. Journal of Sciences of the Earth, 35, 1, 47-52. Feng-Xu,Z, Ling-Shun, M., et al., 2005. Calculating normalized full gradient of gravity anomaly using hilbert transform . Chinese journal of geophysics, vol.48, No.3, 777-784. Hoang Huu Hiep, Nguyen Huu Nam, 2014. Geometrical characteristics and kinetic mechanism of the fault system in the center of Hanoi trough and their role in the formation and destruction of Cenozoic structural traps. Journal of the Oil and Gas, Vol. 9, 26-32. http://www.idm.gov.vn/nguon_luc/Xuat_ban/2008/A305/a24.htm Le Huy Minh, Luu Viet Hung, 2003. Preliminary interpretation for the map of magnetic anomaly on the East Sea and adjacent areas. Journal of Sciences of the Earth, Publisher of Science and Engineering, Ha Noi, 25, 2, 173-181. Le Huy Minh, Luu Viet Hung, Cao Dinh Trieu , 2001. Modern methods from magnetic data analysis applied to Tuan Giao area. Journal of Sciences of the Earth, Publisher of Science and Engineering, Hanoi, 22, 3, 207-216. Le Huy Minh, Luu Viet Hung, Cao Đinh Trieu, 2002. Using the maximum horizontal gradient vector to interpret magnetic and gravity data in Vietnam. Journal of Sciences of the Earth, Publisher of Science and Engineering, 24, 1, 67-80. Le Huy Minh, Vo Thanh Son et al., 2005. The three-dimensional analytic signal method application to interpret the aviation magnetic anomaly map in Tuan Giao. Proceedings of the 4th geophysical scientific and technical conference of Vietnam. Publisher of Science and Engineering 2005. Nguyen Dang Tuc, 2000. Kinematic characteristics of the Red River - Chay River fault zone in Cenozoic, J. Sciences of the Earth, Ha Noi, 22, 3, 174-180. Nguyen Dang Tuc, 2004. The operational characteristics of the red river Fault Zone. http://www.idm.gov.vn/-nguon_luc/Xuat_ban/2004/A285/a69.htm. Nguyen Hiep, 2005. Geology and Vietnam oil and gas resource. Vietnam Oil and Gas Company (Petrovietnam). Oruç, B., Keskinsezer, A., 2008. Structural setting of the Northeastern Biga Peninsula (Turkey) from tilt derivatives of gravity gradient tensors and magnitude of horizontal gravity components. Pure Appl. Geophys. 165, 1913-1927. Oruç, B., Sertcelik, I., Kafadar, O., Selim, H.H., 2013. Structural interpretation of the Erzurum Basin, eastern Turkey, using curvature gravity gradient tensor and gravity inversion of basement relief. J. Appl. Geophys. 88, 105-113. Pedersen, L. B., and T. M. Rasmussen, 1990. The gradient tensor of potential field anomalies: Some implications on data collection and data processing of maps. Geophysics,55, 1558-1566, doi: 10.1190/1.1442807. Pham Nam Hung, Le Van Dung, 2011. The deep structures of Hanoi region and adjacent areas on the basic of gravity data analysis. Journal of Sciences of the Earth, Vol.33, No.2, 185-190. Phan Trong Trinh, 2012. Young tectonics and modern geodynamics in Vietnam sea and adjacent areas. Publisher Natural sciences and technology. Phan Trong Trinh, Hoang Quang Vinh, Nguyen Dang Tuc, Bui Thi Thao, 2000. Young tectonic activity of the Red River Fault Zone and adjacent areas. Journal of Sciences of the Earth, 22, 4, 325-336. Reid,A.B, et al., 2013. Avoidable Euler errors - the use and abuse of Euler deconvolution applied to potential fields. European association of geoscientists & engineers, Geophysical Prospecting. Schneider. M, R.Stolz, S.Linzen, M.Schiffler, A.Chwala, M.Schulz, 2013. Inversion of geo - magnetic full - tensor gradiometer data. Journal of Applied Geophysics 92, 57-67. Vo Thanh Son, Le Huy Minh et al., 2007. Determining the location and depth of the contrast magnetic boundaries by using the 3D analytics signal method and higher derivatives. Proceedings of the 4th geophysical scientific and technical conference of Vietnam, 136-147. Vo Thanh Son, Le Huy Minh, Luu Viet Hung, 2005. Determining the horizontal position and depth of the density discontinuities in the Red River Delta by using the vertical derivative and Euler deconvolution for the gravity anomaly data. Journal of Geological, series A, Vol.287, 3-4, 39-52. Zhang C., M. F. Mushayandebvu et al., 2000. Euler deconvolution of gravity tensor gradient data. Geophysics,65, 512-520, doi: 10.1190/1.1444745.